Study on Scour Prevention Test of Three-Bucket Suction Piles for Offshore Wind Farms in Shapa,Yangjiang - LIU Bo; MA Zhaorong; LIU Xiaojian; GUO Huiqun (Renmin Zhujiang)
By establishing a normal physical model,the scour prevention of the seabed near three-bucket suction piles for offshore wind farms in Shapa,Yangjiang was studied.In view of the scour problem of the suction bucket foundation,protective measures such as riprap,sandbags,and bionic grass were put forward.The results show that when no protection scheme is implemented,the maximum scour depth around the pile in 50 years is 2.34 m;when the protection scheme is implemented,the scour depth around the bucket is significantly reduced and dropped by 44% when sandbags are regularly arranged.The scour depth is reduced by 32% when sandbags are randomly arranged and by 74% when riprap protection is adopted.In addition,the bionic grass not only reduces the scour depth around the pile but also promotes the suspended sand siltation nearby,and the scour depth around the bucket is reduced by about 90% compared with that before protection.